Karyomorphology and Chromosome Number of Four Groups of Gyrinops versteegii (Gilg.) Domke. in Lombok - Widya Iswantari; Tri Mulyaningsih; Aida Muspiah (Jurnal Ilmu Kehutanan)
Lombok has four groups of Gyrinops versteegii i.e. Pantai, Buaya, Madu, and Beringin group. Studies of karyomorphology and the number of chromosomes could be very useful for taxonomy and plant breeding. In this study, the preparation used a root tip squash method. The results obtained from this study: groups of G. versteegii had similar chromosome number (n = 9), and similar metacentric chromosomes. Therefore, the karyotype formula of the four groups of G. versteegii was 2n = 18m. Each group of G. versteegii showed a variation of chromosome size: Pantai group has a size of 0.53 ìm which is the longest than the other three groups: Buaya (0.27 ìm), Madu (0.21 ìm), and Beringin (0.18 ìm).